Brief report: perseverative cognition and behaviors during the early months of the COVID-19 pandemic - Leeanne Qussiny; Cameron R. Wiley; Logan T. Martin; Sarah D. Pressman (Cogent Psychology)
Objective The onset of the COVID-19 pandemic engendered a host of different behavioral responses in key areas such as resource purchasing and compliance with COVID regulations. This study explores why participation in these behaviors may have varied by examining the role of perseverative cognition (i.e., worry, rumination).Method A representative sample of U.S. adults (N = 230, Mage = 45.4, 50% female) was recruited online early in the COVID-19 pandemic (June 2020), approximately three months into safety-related school and business shutdowns. Participants completed a series of questionnaires on COVID-19-related worry, non-specific rumination, and a range of behaviors observed during the early stages of the pandemic (e.g., excessive shopping, purchasing guns, following isolation guidelines). Exploratory principal axis factoring and reliability studies of the newly created COVID-19 worry and behavior scales were performed, followed by an examination of the associations between worrying, ruminating and COVID-19-related early behaviors.Results COVID-related worry and reflective rumination were positively associated with purchasing behavior (i.e., purchasing household items, items for security, and items for entertainment). COVID-related worry was also positively associated with compliance behavior (i.e., watching the news, following government directives strictly, and staying home but contacting family and friends remotely). Brooding rumination was not significantly associated with either type of behavior.Conclusions Perseverative cognition can help explain patterns in COVID-related behaviors, what motivated differences in these behaviors and, thereby, help explain how people coped during this trying time.